2020
DOI: 10.1038/s41419-020-02997-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-196b-5p-mediated downregulation of FAS promotes NSCLC progression by activating IL6-STAT3 signaling

Abstract: Our recent study demonstrated that the QKI-5 regulated miRNA, miR-196b-5p, and it functions as an onco-microRNA in non-small cell lung cancer (NSCLC) by directly targeting GATA6 and TSPAN12. However, the role of miR-196b-5p in NSCLC progression and metastasis still remains unclear. We found that miR-196b-5p promotes lung cancer cell proliferation and colony formation by directly targeting tumor suppressor, FAS. The expression of FAS was significantly downregulated in NSCLC tissue samples and was negatively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
(61 reference statements)
0
27
0
Order By: Relevance
“…FN1 is related to TNM staging, lymph node metastasis and OS and promotes the metastasis of GC cell lines [12]. IL-6-mediated signal transducer and activator of transcription 3 (STAT3) activation can promote the tumorigenesis of non-small-cell lung cancer through the activating NF-κB pathway [16]. The overexpression of POSTN in tumors is an indicator of poor prognosis in colorectal cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…FN1 is related to TNM staging, lymph node metastasis and OS and promotes the metastasis of GC cell lines [12]. IL-6-mediated signal transducer and activator of transcription 3 (STAT3) activation can promote the tumorigenesis of non-small-cell lung cancer through the activating NF-κB pathway [16]. The overexpression of POSTN in tumors is an indicator of poor prognosis in colorectal cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that the expression of miR-196b is up-regulated NSCLC, and is negatively regulated by RNA binding protein QKI-5, a tumor suppressor in NSCLC. miR-196b promotes NSCLC progression and metastasis by targeting the tumor suppressors, TSPAN12, GATA6, and FAS (Liang et al, 2020 ) (Huang et al, 2020 ). However, Tellez et al reported that miR-196b-5p was epigenetically silenced in the premalignant stage of lung cancer, suggesting that tumor-suppressive functions of miR-196b in NSCLC (Tellez et al, 2016 ).…”
Section: Tumor Suppressor and Oncogenic Mirnas In Nsclcmentioning
confidence: 99%
“…miR-20a inhibits the expression of Fas in osteosarcoma cells, thereby facilitating the survival of tumor cells and enhancing their metastatic capacity [ 33 ]. Besides, miR-146a and miR-196b inhibit Fas expression, and ectopic expression of miR-196b causes rapid leukemia [ 34 , 35 ]. In addition, the expression of miR-196b-5p has been shown to possess a significant negative correlation with the expression of Fas in non-small cell lung cancer (NSCLC) [ 35 ].…”
Section: The Role Of Micrornas In Apoptotic Pathwaysmentioning
confidence: 99%
“…Besides, miR-146a and miR-196b inhibit Fas expression, and ectopic expression of miR-196b causes rapid leukemia [ 34 , 35 ]. In addition, the expression of miR-196b-5p has been shown to possess a significant negative correlation with the expression of Fas in non-small cell lung cancer (NSCLC) [ 35 ]. miR-25, which has been observed to directly target DR4 and protect against TRAIL-mediated apoptosis, is upregulated in intrahepatic bile duct cancer [ 36 ].…”
Section: The Role Of Micrornas In Apoptotic Pathwaysmentioning
confidence: 99%